The Students’ Emotional Engagement with Technology-Assisted Self-Regulated Learning Approach in EFL Writing - Fitriani, Fitriani; Mahmud, Murni; Jafar, Muhammad Basri (Indonesian Journal of Learning Education and Counseling, 2024)
This study aims at exploring the emotional engagement of students in the context of technology-assisted self-regulated learning for EFL writing. This study employed a qualitative method with case study blended ethnographic approach. Nine EFL students and 2 EFL lecturers were conveniently recruited, and the data were analyzed using thematic analysis technique. Based on the results, it is evident that students exhibit high levels of interest, enthusiasm, and curiosity in technology-supported learning environments. Their active participation, problem-solving abilities, and eagerness to utilize technological tools reflect their engagement in self-regulated learning processes. Further research on exploring the challenges and barriers associated with technology integration in EFL classrooms would provide practical guidance for educators seeking to maximize the benefits of technology in language learning.